Factorising Green Practices Items - Jamilah Asha’ari, Maryam; Daud, Salina (International Journal of Engineering and Technology, 2018)
Green practices support Malaysia Government to become an advanced economy by accomplishing it in a resilient, low-carbon, resource efficient and socially inclusive manner. Many businesses especially manufacturing companies aim to achieve a sustainable business which can be achieved by successful implementation of green practices. This study aims to establish the green practices dimensions which focus on chemical manufacturing company. Questionnaires were distributed to the employees from middle to top level management in chemical manufacturing company. This study used multistage sampling technique and the data was analysed using partial least square (PLS), SmartPLS version 3. The findings shows that the nine dimensions of green practices which are waste management, sustainable resource management, sustainable design, cleaner production and resource efficiency, sustainable transport, eco-labelling, sustainable procurement, sustainable marketing and sustainable lifestyles are confirmed. It was found that all of the dimensions have AVE value higher than 0.5, composite reliability higher than 0.7 and loading higher than 0.7.Â